Modernity and colonialism: on the historical-sociological blindness of the theories of modernity: SOBRE A CEGUEIRA HISTÓRICO-SOCIOLÓGICA DAS TEORIAS DA MODERNIDADE; ON THE HISTORICAL-SOCIOLOGICAL BLINDNESS OF THE THEORIES OF MODERNITY - Bavaresco, Agemir; Danner, Leno Francisco; Danner, Fernando (Sofia, 2017)
This paper criticizes the historical-sociological blindness found in contemporary theories of modernity (as in those of Weber and Habermas) in order both to construct a sociological model for the process of Western modernization and to formulate a normative notion of cultural modernity which can favor the development of a critical social theory which is correlatively sociological and philosophical. The historical-sociological blindness regarding the theoretical-political reconstruction of the process of Western modernization is basically characterized by the separation between European cultural modernity and European social-economic modernization, which leads to the notion that European culture is not directly linked to social and economic modernization. Likewise, Western modernization is fundamentally an autonomous and endogenous constitutive process, bearing no correlation with other cultures-societies, as seen in the lack of references to the fact of colonialism. Such a separation between culture and social systems or institutions results in European cultural modernity becoming a pure normative concept with no direct relations to both social and economic modernization and colonialism. That is the reason why, according to Habermas, a critical and universalistic normative concept both to a critical social theory and its political praxis, as to international politics, is allowed. The central argument of this paper is that the theories of modernity cannot provide a normative paradigm to a critical social theory based on cultural modernity due to this historical-sociological blindness. Therefore, the elaboration of a normative concept for critical social theory should start by unveiling, denouncing and deconstructing the historical-sociological blindness of these contemporary theories of modernity.